Fear of violence as an indicator of risk in probation work. Its impact on staff who work with known violent offenders - O'Beirne, Maria (The British journal of criminology, 2004)
In 2001, the Home Office launched the Offender Assessment System to help probation and prison staff predict whether known violent offenders will reoffend. One of the paradoxes of a system that predicts future risk of offending is its failure to appraise the fear of staff working with these offenders. In this paper we look at the ways in which fear of violence is managed by probation staff in the course of their work. We consider the impact of fear upon work practices and relationships with colleagues, management and clients. We argue that offender risk assessments need to be cognizant of the extent to which fear may act as a warning sign to management of staff vulnerability and their capacity to work with those clients in accordance with their responsibilities